Hortus Kewensis, or, A catalogue of the plants cultivated in the Royal Botanic Garden at Kew - Aiton, William, 1731-1793.; Aiton, William Townsend, 1766-1849. (London : Printed for Longman, Hurst, Rees, Orme, and Brown, 1810)
Contains 11,013 species of which 300 are Australian species, 116 of them sourced from Flinder's circumnavigation of Australia, 1801-1803, in the Investigator. The catalogue gives brief descriptions in Latin according to the Linnean style, not only of plants grown at Kew but also of almost all the species then cultivated in England. In addition it records the native country of each species, date of introduction and by whom introduced.
Library's N set is untrimmed.
"Books quoted": v. 1, p. [xv]-xl.
Keywords: Royal Botanic Gardens, Kew -- Catalogs; Botany -- Catalogs and collections -- Great Britain -- Kew -- Early works to 1800.; Botanical gardens -- Great Britain -- Kew -- Catalogs